Analysis of body composition in the indigenous population of Nueva Loja: perspective for health and well-being in 2024 - Vaca Auz, Adela Janet; Rosero Ortega, Nayeli Liseth; Revelo Villareal, Sonia Dayanara; Méndez Carvajal, Erika; Silva Encalada, Carlos Mauricio (SATHIRI, 2024)
The measurement of anthropometric parameters can be considered as a significant predictor of certain chronic metabolic diseases; therefore, we sought to determine the body composition of the indigenous population of the city of Nueva Loja, province of Sucumbíos. Descriptive cross-sectional study, the sample consisted of 101 indigenous adults between 18 and 47 years of age, selected by non-probabilistic snowball sampling. Weight and height were taken following the ISAK protocol, BMI was calculated with the Quetelet formula under the consensus of the Spanish Obesity Society (SEEDO) and for the measurement of MG, MM, MGV a bioimpedance scale was used, complemented with a questionnaire that included socio-demographic and cultural variables of interest. The data were analyzed in IBM SPSS statistic for the calculation of frequencies, mean percentages and standard deviation. The mean BMI was 28.86 ± 9.01 kg/m2 in men and 26.46 ± 5.22 kg/m2 in women; on the other hand, the mean fat percentage was 28.2 ± 9.5 in men and 37.4 ± 8.1 in women; this in percentages indicated that 48.51% were overweight according to BMI and 36.63% had very high fat values. This leads to the conclusion that Amazonian indigenous adults present a risk profile for developing several diseases in the future if adequate nutritional control is not implemented through healthy eating practices.